2019
DOI: 10.1177/2333794x19828311
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Early Repolarization Pattern Anomalies Among Children and Adolescents With and Without Attention-Deficit Hyperactivity Disorder: A Community Observational Study

Abstract: Our research had 2 aims, first, to determine if electrocardiographic early repolarization pattern anomalies (ERPAs) were more likely present among children and adolescents diagnosed with attention-deficit hyperactivity disorder (ADHD; n = 416) when compared with non-ADHD children (n = 187), and second, to asses if ADHD patients whose parents report severe ADHD psychometric scores were more likely to have ERPA in their surface ECG (electrocardiography) when compared with other ADHD patients with mild to moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The IRB committee agreed with our request to waive the need for ethics approval and the need to obtain informed consent for the medical records review, data analysis, and publication of the retrospectively obtained and anonymized data for this noninterventional study. Our methodology had been previously published (Isart et al 2019 ). Our population research sample ( N = 2366) included two groups: Group 1 with children and adolescents (5–18 years of age) evaluated for ADHD at an urban community clinic (Kids ‘N Teen Clinics, PA, Houston, TX) who had an ECG done ( n = 418, 2008–2017); and Group 2 is the historical control group that included 1948 children and adolescents of 5–18 years of age from a large group of healthy children and adolescents who were subjects in pharmaceutical company-sponsored clinical trials with centralized management and interpretation of their ECGs by a core ECG laboratory (Covance, Reno, NV, 2003–2005, Table 1 ), reported by Mason et al ( 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…The IRB committee agreed with our request to waive the need for ethics approval and the need to obtain informed consent for the medical records review, data analysis, and publication of the retrospectively obtained and anonymized data for this noninterventional study. Our methodology had been previously published (Isart et al 2019 ). Our population research sample ( N = 2366) included two groups: Group 1 with children and adolescents (5–18 years of age) evaluated for ADHD at an urban community clinic (Kids ‘N Teen Clinics, PA, Houston, TX) who had an ECG done ( n = 418, 2008–2017); and Group 2 is the historical control group that included 1948 children and adolescents of 5–18 years of age from a large group of healthy children and adolescents who were subjects in pharmaceutical company-sponsored clinical trials with centralized management and interpretation of their ECGs by a core ECG laboratory (Covance, Reno, NV, 2003–2005, Table 1 ), reported by Mason et al ( 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…Power analysis, with β =0.20 and α =0.05, was conducted assuming a difference of 20% based on the previous studies [10,11]. We had a projected sample size of approximately 43 patients (total of 172 subjects).…”
Section: Power Analysismentioning
confidence: 99%
“…Recently, there have been reports on psychiatric disorders and Early repolarization pattern (ERP). It has been reported associations between psychiatric disorders such as Attention-deficit hyperactivity disorder (ADHD) [10, 11], serious mental illness and ERP. [12] These reports suggest the associations between ERP and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 17, 2020. ; https://doi.org/10.1101/2020.07.16.20155838 doi: medRxiv preprint 5 sudden cardiac death [11,12]. Recently, it has been reported that there are associations between ERP and attention-deficit hyperactivity disorder [13,14],and the patients with suicidal risks [15].…”
Section: Introductionmentioning
confidence: 99%
“…ERP and J-point elevation pattern, which are not uncommon and often observed in younger and healthier people [10], are arrestive electrocardiographic patterns associated with sudden cardiac death [11,12]. Recently, it has been reported that there are associations between ERP and attention-deficit hyperactivity disorder [13,14],and the patients with suicidal risks [15]. Moreover, Fitzgerald et.al reported that Patients with serious mental illness, especially schizophrenia/schizoaffective disorder, exhibit a significantly high rate of abnormal late potentials on Signal-averaged electrocardiogram (SAECG) and ERP [16].…”
Section: Introductionmentioning
confidence: 99%